How personal values and critical dispositions support digital citizenship development in higher education students - Assante, Gabriela Monica; Popa, Nicoleta Laura; Momanu, Mariana (Frontiers in Psychology, 2022)
The virtual environment’s expansion and role in young people’s lives accentuate the need for developing transversal competences such as digital citizenship. The process may be supported by personal resources like personal values and critical thinking dispositions. With this study on 536 young students’ students aged 18 to 26 (M = 20.85, SD = 1.60), we analysed the relationship between two adjacent personal values, universalism and self-direction, and students' digital citizenship. Moreover, we examined the role of critical thinking dispositions, namely learning orientation, and cognitive integrity in supporting digital citizenship development. Following structural equation modelling (SEM) analyses, the results show that universalism and learning orientation significantly positively influence digital citizenship, whereas cognitive integrity has a negative effect. Further, personal values positively associate with critical thinking dispositions.